Modelo ProLab: Lenteburger, una propuesta sostenible que contribuirá a combatir la malnutrición - Rodríguez Toribio, Janeth Estefany (2024)
This research work addresses the critical social problem of providing healthy nutrition to children in contexts of budget limitations due to the existence of child malnutrition in our country. Aware of the importance of products that are pleasant in taste and rich in nutritional value, parents are prevented by financial restrictions from opting for dietary supplements. The proposed solution consists of the development of Lenteburger, a pre-cooked hamburger made with chicken blood and lentils, offering an accessible alternative and pleasant flavor. The main objective is to contribute to the reduction of child malnutrition, especially in children aged 1 to 5 years, aligning with Sustainable Development Goal (SDG) 2, specifically goal 2.2. To ensure the desirability, feasibility and viability of the project, hypothesis tests and usability tests were carried out with users, obtaining results that indicated a significant willingness of consumers to purchase the product. In addition, analyzes and simulations were carried out under various scenarios, resulting in a projected net present value (NPV) of $1,001,951 and an internal rate of return (IRR) of 89%. Finally, with an initial investment of $85,931 and a projected social NPV of $6,213,604, it is supported that this innovative proposal not only seeks to improve children's health, but also promotes a sustainable and responsible approach to guarantee access to nutritious diets and a commitment to improving the quality of life of the community and the environment.